RANCANG BANGUN DAN UJI KINERJA MEKANISME CRANK-SLIDER PADA ALAT RESUSITASI JANTUNG PARU OTOMATIS BERBASIS ARDUINO MEGA 2560 - Rafiuddin Syam; Muhammad Awaluddin; Churnia Sari (LPPM Universitas Negeri Jakarta, 2025)
Sudden cardiac arrest requires immediate cardiopulmonary resuscitation (CPR) with a compression depth of 5–6 cm and a rate of 100–120 compressions per minute according to the 2020 American Heart Association (AHA) guidelines. Manual CPR is prone to declining consistency due to rescuer fatigue, so an automatic CPR device is needed to maintain accurate and consistent compressions. This study designs and evaluates the performance of a crank-slider chest-compression mechanism in an automatic CPR device based on an Arduino Mega 2560 with a lead-screw-and-NEMA17-stepper lifter to adjust the zero position for patient chest-size variation, assisted by a Hall-Effect incremental rotary encoder. Product development follows the VDI 2221 method, while the speed of the PG45 DC motor is regulated by a PID controller tuned using Particle Swarm Optimization (PSO) with an ITAE objective function. Optimization yielded Kp = 5.0000, Ki = 2.9519, and Kd = 0.5000 with a minimum ITAE of 2.3586. A 28 mm crank radius produced a 56 mm (5.6 cm) compression stroke consistent with the AHA standard. Physical testing on a CPR manikin showed an RMSE of 30.12 between the ideal simulated speed (120 RPM) and the actual implementation (average 91.95 RPM), attributed to the manikin chest wall's viscoelastic resistance and internal mechanical friction under peak load. The developed device produced a compression depth consistent with the AHA standard, although motor-speed performance in the physical implementation still needs improvement.